2011
DOI: 10.1002/ijc.26223
|View full text |Cite
|
Sign up to set email alerts
|

αLβ2 Integrin is indispensable for CD8+ T‐cell recruitment in experimental pancreatic and hepatocellular cancer

Abstract: Recruitment of activated leukocytes from peripheral blood into the tumor tissue is a crucial step of the immune response, which is controlled by the interaction between specific adhesion molecules such as endothelial ICAM-1 and leukocyte b 2 -integrins. Although attenuated expression of adhesion molecules on tumor endothelium has been proposed to represent a mechanism, which suppresses the intratumoral leukocyte infiltration, the relevance of adhesion molecules for leukocyte recruitment in tumor tissue is poor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 41 publications
3
20
0
Order By: Relevance
“…Several adhesion molecules, such as E-selectin, vascular cellular adhesion molecule (VCAM)-1 and ICAM-1, exhibit increased expression in the liver during metastatic invasion (22). Among them, ICAM-1 mediates several stages of the metastatic cascade, including the adhesion of tumor cells to the endothelial wall (23)(24)(25), endothelial cell activation of pro-metastatic signaling pathways (26)(27)(28), tumor cell extravasation (23,29), the recruitment of immune cell populations (28,30,31), the pro-angiogenic response (32) and the transdifferentiation of stellate cells during the desmoplastic response (33,34). This review will focus on the role of ICAM-1 during the different events of the metastatic cascade that drives colonization of the liver by circulating tumor cells, and how it modulates the liver microenvironment to facilitate metastasis.…”
Section: Introductionsupporting
confidence: 45%
“…Several adhesion molecules, such as E-selectin, vascular cellular adhesion molecule (VCAM)-1 and ICAM-1, exhibit increased expression in the liver during metastatic invasion (22). Among them, ICAM-1 mediates several stages of the metastatic cascade, including the adhesion of tumor cells to the endothelial wall (23)(24)(25), endothelial cell activation of pro-metastatic signaling pathways (26)(27)(28), tumor cell extravasation (23,29), the recruitment of immune cell populations (28,30,31), the pro-angiogenic response (32) and the transdifferentiation of stellate cells during the desmoplastic response (33,34). This review will focus on the role of ICAM-1 during the different events of the metastatic cascade that drives colonization of the liver by circulating tumor cells, and how it modulates the liver microenvironment to facilitate metastasis.…”
Section: Introductionsupporting
confidence: 45%
“…Recent findings demonstrated that integrins are involved in the regulation of cell migration, such as lymphocytes infiltration in inflammation and tumors (11,12). Integrin α4 is a subunit of vascular cell adhesion molecule-1 (VCAM-1) receptor, very late antigen-4 (VLA-4).…”
Section: Introductionsupporting
confidence: 49%
“…The adhesion molecule L1CAM (CD171), which increases during PDAC progression in the ductal epithelium [111], also appears to be involved in reducing CD4 + T cell proliferation and in inducing CD69 expression, probably because it mediates the release of soluble factors promoting the generation of CD4 + T cells with a CD69 + phenotype [105]. Another PDAC-associated adhesion molecule, an ICAM-1 receptor α L β 2 integrin (also known as LFA-1 or CD11a/CD18), regulates CD8 + T cell recruitment: only its knockout results in a marked impairment of CD8 + T cell infiltration in experimental pancreatic tumors in mice, probably because its lack of expression impairs T cells activation and differentiation [112]. Overexpression and secretion by activated PSCs of β-galactoside-binding protein Galectin-1 (Gal-1), another molecule that mediates immunosuppression in PDAC by targeting T cell, increases Th2 and decreases Th1 cytokines, inducing CD4 + and CD8 + T cell apoptosis [113].…”
Section: Immune Effector Cellssupporting
confidence: 39%